Decomposition of Heart Rate Variability Spectrum into a Power-Law Function and a Residual Spectrum - Kuo, Jane; Kuo, Cheng-Deng (Frontiers in Cardiovascular Medicine, 2016)
The power spectral density (PSD) of heart rate variability (HRV) contains a power-law relationship that can be obtained by plotting the logarithm of PSD against the logarithm of frequency. The PSD of HRV can be decomposed mathematically into a power-law function characterized by the slope and Y-intercept of linear regression, and a residual HRV spectrum (rHRV). Almost all rHRV measures are significantly smaller than their corresponding HRV measures except the normalized high-frequency power (nrHFP). The power-law function can be characterized by the slope and Y-intercept of linear regression. Almost all HRV measures except the normalized low-frequency power (nLFP) have significant correlations with the Y-intercept, while almost all rHRV measures except the total power (rTP) do not. Though some rHRV measures still correlate significantly with the age of the subjects, the rTP, high-frequency power (rHFP), nrHFP and low-/high-frequency power ratio (rLHR) do not. In conclusion, the clinical significances of rHRV measures might be different from those of traditional HRV measures. The Y-intercept might be a better HRV measure for clinical use because it is independent of almost all rHRV measures. The rTP, rHFP, nrHFP and rLHR might be more suitable for the study of age-independent autonomic nervous modulation of the subjects.